Dicentrine Analogue-Induced G2/M Arrest and Apoptosis through Inhibition of Topoisomerase II Activity in Human Cancer Cells - Lin, Huei-Fang; Huang, Huey-Lan; Liao, Jyh-Fei; Shen, Chien-Chang; Huang, Ray-Ling (Planta Medica, 2015)
Lindera megaphylla has been traditionally used as an antineoplastic and wound healing remedy. We previously demonstrated the antitumor effects of D-dicentrine, a natural aporphine alkaloid from the root of L. megaphylla. To generate analogues, series of phenanthrene alkaloids from D-dicentrine were synthesized by degradation with ethyl chloroformate in pyridine, base hydrolysis, and N-alkylation. In this study, we demonstrated that one of the synthesized D-dicentrine analogues (here after designated as analogue 1) exhibited more potent cytotoxic effects than D-dicentrine in colon adenocarcinoma, hepatoma, leukemia, and epidermoid carcinoma cells. We performed cell cycle and apoptotic analysis by flow cytometry, an apoptotic DNA detection ELISA assay, and topoisomerase II activity by the kinetoplast DNA concatenation assay for studying their cytotoxic mechanisms. We found that both D-dicentrine and analogue 1 induced apoptosis and G2/M arrest in HL-60 leukemia cells. The percentage of apoptotic cells induced by analogue 1 was 4.5-fold higher than that induced by D-dicentrine as evident from measuring the amount of histone-bound DNA fragments. Moreover, we found that analogue 1 was 28-fold more potent than D-dicentrine for inhibition of topoisomerase II activity by the kinetoplast DNA concatenation assay. Our findings indicate that D-dicentrine analogue 1 is very promising as a potential antitumor agent for future study.
Keywords: Lindera megaphylla; Lauraceae; D-dicentrine; dicentrine analogues; cytotoxicity; apoptosis; topoisomerase II inhibitor; cell cycle arrest